2022
DOI: 10.1126/sciadv.abn9440
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy of glioblastoma explants induces interferon-γ responses and spatial immune cell rearrangements in tumor center, but not periphery

Abstract: A patient-tailored, ex vivo drug response platform for glioblastoma (GBM) would facilitate therapy planning, provide insights into treatment-induced mechanisms in the immune tumor microenvironment (iTME), and enable the discovery of biomarkers of response. We cultured regionally annotated GBM explants in perfusion bioreactors to assess iTME responses to immunotherapy. Explants were treated with anti-CD47, anti–PD-1, or their combination, and analyzed by multiplexed microscopy [CO-Detection by indEXing (CODEX)]… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…PRRS was calculated for each type of TAMs. A previous study suggested that higher interferon γ (IFNγ) response was associated with immunotherapy response in GBM, and IFNγ could modulate the immune cell composition in the tumor center ( 44 ). Intriguingly, a significantly higher PRRS was found in interferon-signature microglial-TAM (IFN_MgTAM) than in non-interferon-signature microglial-TAM (MgTAM) ( Figure 7H, I ).…”
Section: Resultsmentioning
confidence: 99%
“…PRRS was calculated for each type of TAMs. A previous study suggested that higher interferon γ (IFNγ) response was associated with immunotherapy response in GBM, and IFNγ could modulate the immune cell composition in the tumor center ( 44 ). Intriguingly, a significantly higher PRRS was found in interferon-signature microglial-TAM (IFN_MgTAM) than in non-interferon-signature microglial-TAM (MgTAM) ( Figure 7H, I ).…”
Section: Resultsmentioning
confidence: 99%
“…Response to the antidepressant Vortioxetine, the most promising preclinical candidate, was particularly aligned with aggressive GSC morphotypes present in patients with poor prognosis. These efforts contribute to the nascent community of glioblastoma research focusing on the investigation of patient-derived tumor explants that facilitate translational investigation of complex tumor behavior, including the development of genetically characterized patient cultures, organoid biobanks, and regionally annotated samples 29,[77][78][79][80][81][82] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many studies have shown that the cultivation of patient-derived biopsies in perfusion bioreactors can maintain the same gene expression profile and drug resistance patterns recorded in vivo [ 95 ]. Models of colon cancer [ 96 , 97 ], breast carcinoma [ 95 , 98 , 99 , 100 ], ovarian cancer [ 101 ], bone metastatic prostate cancer [ 102 ], Erwin sarcoma [ 103 , 104 ], leukemia [ 105 , 106 ], and glioblastoma [ 107 ] have been engineered using perfusion bioreactors.…”
Section: 3d Modelsmentioning
confidence: 99%
“…There were then perfused with a mix of cell culture media and growth factors. In this model, it was shown that a subset of cells was prone to the emission of IFNγ and consequently to shifts in immune cell composition within specified tissue portions; immune responder and non-responder subpopulations could then be identified [ 107 ].…”
Section: 3d Modelsmentioning
confidence: 99%